Caso para diagnóstico Case for diagnosis - Carolina Tomiyoshi; Adma Silva de Lima Wojcik; Elisa Milani Oba Vencato; Guilherme Ribas Taques; José Fillus Neto; Fabiane Andrade Mulinari Brenner (Sociedade Brasileira de Dermatologia, 2010)
A esclerodermia localizada (EL) ou morfeia é uma doença crônica do tecido conjuntivo, de provável etiologia autoimune, que tem como base alterações na síntese e deposição do colágeno, representadas clinicamente por lesões cutâneas escleróticas. Algumas placas podem apresentar coloração amarelada ou xantocrômica, causando confusão diagnóstica. Este artigo relata o caso de uma adolescente, com concomitância de lesões eritematosas e xantocrômicas, ambas manifestações clínicas da doença. Localized scleroderma or morphea is a chronic disease of the connective tissue. Its etiology may be autoimmune and the condition results from a disturbance in collagen synthesis and deposition, clinically represented by sclerotic skin lesions. Some plaques may be yellowish, which can be misleading at diagnosis. This article reports the case of an adolescent girl who concomitantly presented erythematous lesions and yellowish lesions, both of which constitute clinical manifestations of the disease.